Biocatalyst immobilization : foundations and applications - Ferreira, Maria Lujan (Foundations and frontiers in enzymology series., 2023)
Biocatalyst Immobilization: Foundations and Applications provides a comprehensive overview of biocatalytic immobilization processes, as well as methods for study, characterization and application. Early chapters discuss current progress in enzyme immobilization and methods for selecting and pretreating enzymes prior to immobilization, with an emphasis on navigating common challenges and employing enzyme supports and post immobilization treatments to impact enzymatic activity. Process-based chapters instruct on measuring and reporting on enzyme immobilization efficiency, protein final content, quantification of reaction products, and the use of nanomaterials to characterize immobilized enzymes.